The effect of partial and total replacement of marble waste as coarse aggregate in concrete mix on mechanical properties - Abdel Nader Khalil Aldabar; Abdulmutaleb Mohamed Ahmidan (African Journal of Advanced Pure and Applied Sciences, 2024)
Waste from the manufacture of building materials (marble) causes many problems in the environment, which requires research into ways to benefit from it around the world. In some developing countries, such as Libya, there is no management of industrial solid waste because local agencies (cleaning agencies) are limited only to cleaning Streets and residential waste transportation only. This may further exacerbate the problem of solid industrial waste accumulation around factory sites. As the remains of marble manufacturing waste are increasing, they may be useful if used as fine or coarse aggregate in cement mortar and concrete. Using marble waste can solve the problem of aggregate shortage, and on the other hand, the cost of building materials. The use of alternative components is now a source of global concern, so new sources must be researched and explored to produce building materials that achieve sustainability and are environmentally friendly. In this study, marble waste was used as an alternative to coarse aggregate in the design of regular concrete. Concrete mixtures containing marble waste were designed in proportions (0%, 25%, 50%, 75%, 100%) and tests were conducted, including absorption and specific gravity tests. The volumetric weight of marble, slump and compressive strength to study its effect on concrete. As it was observed from the compressive strength test of concrete samples when replacing coarse aggregate with marble aggregate, no increase was observed when replacing 25%, but rather it decreases by (7.56%), while it begins to increase when replacing 50% at a rate of (15.39%), as well as in the modulus of elasticity at a rate of (8%). Then it gradually decreases to 75% and 100% replacement rates.